Pengaruh Asimetri Informasi, Profitabilitas, dan Pertumbuhan Perusahaan Terhadap Nilai Perusahaan - Ilham Pauzi; Barlia Annis Syahzuni (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study investigates the influence of information asymmetry, profitability levels, and business growth on company value the transportation and logistics sector. The sample comprises nineteen companies listed on the Indonesia Stock Exchange from 2022 to 2024, totaling fifty-seven observations. Information disparity proxied by the bid-ask spread, profitability is measured via net profit margin, and corporate growth is calculated based on total asset increases. Company value is represented by the Tobin’s Q. Data analysis followed a panel data approach, with model selection conducted through Chow and Hausman tests. The estimation utilized a Fixed Effect Model integrated with robust standard errors to ensure the model passed simultaneous significance tests while producing more accurate estimation parameters. Research findings indicate that the three independent variables simultaneously affect business value, as evidenced by the significant F-test result. Partial testing reveals that profitability exerts significant positive impact, information asymmetry shows no influence, whereas corporate growth demonstrates a significant negative effect. These results suggest that increased profits do not necessarily enhance market valuation if investors doubt performance sustainability. Practically, firms must balance profitability and sustainable growth strategies to maintain investor confidence. Future research should incorporate corporate governance as monitoring mechanism to better understand firm value determinants.